Clinical characteristics and mutation spectrum in 33 Chinese families with familial exudative vitreoretinopathy. (31st December 2022) - Mao, Jianbo; Chen, Yijing; Fang, Yuyan; Shao, Yirun; Xiang, Ziyi; Li, Hanxiao; Zhao, Shixin; Chen, Yiqi; Shen, Lijun
Abstract: Objective: To explore the clinical manifestations and search for the variants of six related genes ( LRP5, FZD4, TSPAN12, NDP, KIF11 and ZNF408 ) in Chinese patients with familial exudative vitreoretinopathy (FEVR), and investigate the correlation between the genetic variants and the clinical characteristics. Patients and methods: Clinical data, including the retinal artery angle, acquired from wide-field fundus imaging, structural and microvascular features of the retina obtained from optical coherence tomography (OCT) and OCT angiography (OCTA) were collected from 33 pedigrees. Furthermore, mutation screening was performed. Variants filtering, bioinformatics analysis and Sanger sequencing were conducted to verify the variants. Results: Twenty-one variants were successfully detected in 16 of 33 families, of which 10 variants were newly identified. The proportion of variants in LRP5, FZD4, TSPAN12, NDP and KIF11 was 38.1% (8/21), 33.3% (7/21), 19.1% (4/21), 4.8% (1/21) and 4.8% (1/21), respectively. Three new variants were considered to be pathogenic or likely pathogenic. The FEVR group tended to exhibit a smaller retinal artery angle, higher incidence of foveal hypoplasia and lower vascular density compared to the control group. Patients who harboured variants of FZD4 exhibited greater severity of FEVR than those with LRP5 variants. However, those who harboured LRP5 variants tended to possess lower foveal vascular density. Conclusions: Six known pathogenic genes were screened in 33 pedigrees with FEVR in our study, which revealed 10 novel variants. These findings enrich the clinical features and mutation spectrum in Chinese patients with FEVR, revealing the genotype-phenotype relationship, and contributing to the diagnosis and treatment of the disease. Key messages: We identified 21 variants in 5 genes ( LRP5, FZD4, TSPAN12, NDP and KIF11) associated with FEVR, 10 of which are novel (three were pathogenic or likely pathogenic). The proportion of variants was the highest for the LRP5 gene. FZD4 variants may be responsible for greater FEVR severity than LRP5 variants.